Assistance in Determining the Selling Price of Ecoprint Batik (HR. Ambar Batik Bayat, Wedi, Klaten) - Yane Puspito Sari (Asian Journal of Community Services, 2022)
Ecoprint has been known for a long time, but ecoprint is experiencing a rapid increase at this time because it is considered to have economic value and is easy to manufacture. In addition, the fabric produced from the ecoprint technique has a more attractive appearance and is of high value because the process is made by hand. Ecoprint is defined as the process of transferring colors and shapes to fabrics through direct contact. The ecoprint technique is a development of ecofashion, to produce eco-friendly fashion products. HR. Ambar Batik, is one of the batik craftsmen who innovate to produce batik with natural materials. So far, Ambar batik produces hand-drawn batik and stamped batik. With the ecoprint which is now starting to become a fashion trend, Ambar batik is trying to produce ecoprint batik to be able to compete with ecoprint batiks that are starting to appear among batik entrepreneurs. The purpose of this community service is to determine the raw materials for making ecoprints, see the process of making ecoprints, increase the knowledge of batik craftsmen in developing their creativity in dealing with fashion trends, determine the selling price of ecoprint batik.